The behaviour of culinary arts interns in relation to food safety and hygiene practices / Mohammad Halim Jeinie - Jeinie, Mohammad Halim (2021)
There are significant concerns among researchers in elevated food safety and hygiene to assuring safe food practices in the workplace. Specifically, a persistent pattern of foodborne incidence has triggered an alarming question of the sustainable operation for retail foodservice operations such as restaurants, hospitals, schools, and catering. Indeed, a culinary program is designed to produce competent food handlers in holistic upon them entering the food industry. Furthermore, culinary intern undergoes industry attachment among various food service operation as a condition for graduation. This study empirically measuring the impact of the conceptual mind Food Safety and Hygiene (FSH) toward the actual behaviour of implementation in the workstation. Based on the result of quantitative studies, a mixed-method approach using qualitative through questionnaire survey (culinary student) and qualitative through interview and observation (focus group) are applied in this study further investigate to understand the phenomena. One hundred ninety-four (194) culinary students respond to assess the present status of knowledge, attitude, and practice were successfully survey. In contrast, 18 returnees’ culinary students from industrial attachment were assessed by interview and questionnaire on food hazards knowledge impact the real practice. Finally, 18 final year students participate in the real-time observation in obtaining the valuable insights and causal correlation between the variable of interest or investigated variables. The qualitative information through the interview was interpreted using thematic analysis. For the quantitative data gathered, several predetermined tests (reliability), the descriptive (frequency and central tendency), and inferential statistical analyses were conducted. Some clear insights appeared in this study that by understand of food hazards towards the consequent towards the risk of FSH determinant (wash, clean, use and inspect) which are link to the appropriate hand washing, use of gloves, preventions of food hazards, poor knowledge of pathogen-associated with diseases causes agent, critical temperature knowledge for storage and the effective of ongoing training. This finding is further strengthened with the process of observation to validate the phenomena. In theory, KAP impact student on the conceptual mind on food safety and hygiene in the higher learning education systems somehow the theory support but not effective enough. In higher learning, culinary intern was in the process to develops their treats as professional chef, besides focusing KAP, a mechanisms and effective observations must be employed to produce positive results. These positive and promising indicators from the practical aspects give varying consequences and implementations, particularly in designing training modules in the culinary module.